ALGORITHM FOR ORGANIZING SHADOW PAYROLL UNDER CONDITIONS OF INTERNATIONAL EMPLOYEE MOBILITY IN THE USA (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the context of growing cross-border labor mobility and the expansion of remote work models, multinational companies increasingly face challenges related to payroll administration and tax compliance in multiple jurisdictions. One of the most effective tools for managing such complexity is the shadow payroll model, which enables accurate tax reporting without the need to establish a legal entity in the host country. The article focuses on the specifics of organizing shadow payroll for companies that engage foreign employees in the United States, especially in the absence of local financial infrastructure.The purpose of the article. The main objective of the study is to develop and substantiate a structured algorithm for the implementation of shadow payroll in international companies operating in the U.S. labor market. The algorithm aims to ensure tax compliance under the legislation of both the home and host countries while minimizing legal and financial risks.Methods. The methodological approach combines comparative legal analysis, synthesis of international regulatory practices, and empirical modeling based on real case studies. Special attention is paid to IRS documentation (e.g., Publications 15 and 519), OECD tax guidelines, and bilateral agreements on the avoidance of double taxation. The algorithm was developed using elements of fiscal modeling, HR data synchronization, and digital payroll automation.Results.The study resulted in the design of a seven-step algorithm for implementing shadow payroll, which includes: (1) determining the fiscal status of the employee, (2) establishing a dual home/host payroll structure, (3) automating payroll calculations and currency conversions, (4) organizing centralized reporting in accordance with U.S. and local standards, (5) ensuring cooperation with tax and HR advisors, (6) controlling the source of wage disbursement in line with IRS requirements, and (7) classifying compensation components. The model has been tested in practice through payroll projects involving employees from Germany and Austria. The algorithm has demonstrated high efficiency in ensuring compliance without creating a legal presence in the U.S.Conclusions. Shadow payroll is positioned as a hybrid solution at the intersection of taxation, labor law, and international HR management. Its implementation requires a multidisciplinary approach that integrates accounting, digital reporting, and international tax planning. The algorithm proposed in the article can serve as a methodological foundation for companies expanding into global markets without permanent establishments abroad. Future research directions include the development of regulatory frameworks in Ukraine, standardization of payroll procedures in a cross-border context, and further exploration of digital tools for managing international payroll operations.
Keywords: shadow payroll, double taxation, international taxation, transnational mobility, compliance